Acoustic absorption of a metamaterial panel: Mechanism, boundary effect and experimental demonstration. (15th December 2021) - Zhao, Honggang; Zheng, Qiquan; Wang, Yang; Cao, Junhui; Wang, Chao; Wen, Jihong
Abstract: The present paper investigates absorption of a metamaterial panel composed of a flexible micro-perforated panel attached periodically with local resonators. It gains good agreement between the results of the theoretical prediction and finite element simulation for the metamaterial panel while considering the vibroacoustic coupling between the sound excitation and the plate vibration. Both theoretical and finite element simulation results show that the local resonator can tune the acoustic surface impedance at desired frequency. The boundary effect of the metamaterial panel under the simply supported or clamped condition at all four edges is investigated. It shows that new absorption peak can be acquired differently under various boundary conditions. The absorption mechanism is further revealed by the displacement pattern and the surface impedance. Finally, a sample of four-edge clamped metamaterial panel is designed and fabricated. The experiment and simulation results validate the theoretical prediction.